Financial Decision-Making Efficiency and Computerized Accounting Systems: A Study of SMES In Ghana - Agbozo, Lewi Amanor; Derashri, Dr. Purvi Dipen (International Journal of Accounting and Economics Studies, 2025)
This research examines how computerized accounting systems (CASs) are adopted and used by SMEs in Ghana, in a bid to understand their influence on the efficiency of financial decision-making and overall performance. The research adopted a quantitative method; 625 SMEs were sampled through questionnaires. Correlation and regression analyses were performed for the quantitative data. From the analysis, there is a positive correlation of statistical significance between the adoption of CAS and financial decision-making efficiency and performance. Technical expertise, financial resources, and government support were found to be the most influential factors in determining its adoption. The research identifies the critical role of CAS within SMEs in Ghana and addresses supportive policies and adequate resources necessary for its adoption. This study adds to the body of knowledge by providing an insight into the unique context of the adoption of CAS by Ghanaian SMEs and puts forward some recommendations for policy and stakeholders to better integrate technologies for well-structured financial management practices.